Hematochezia in a 6-year-old girl: An unusual cause (Indian Journal of Case Reports, 2022)
Anorectal disorders, anal fissures, and distal polyps are the most common causes of hematochezia in children. However, inflammatory bowel disease (IBD), even though quite rare in children, can present with an isolated per rectal bleeding. Early onset IBD is described in patients younger than 10 years of age; however, these are rare instances of even neonates presenting with IBD. Here, we report the case of a 6-year-old girl who presented with episodes of per rectal bleeding for several months with severe anemia and malnutrition and was also found to have an anteriorly displaced anus. She underwent colonoscopy which revealed features suggestive of ulcerative colitis which was eventually confirmed by biopsy. She was treated with corticosteroids and aminosalicylate, namely, Mesalamine. Later, the patient was treated with Azathioprine which resulted in the complete resolution of symptoms and improvement in nutritional status that was evident on regular follow-ups. IBD in children younger than 10 years of age is a rare entity and requires a strong suspicion for diagnosis.